1992
DOI: 10.1111/j.1467-8535.1992.tb00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing language and cognition in young children with Logo

Abstract: A Logo intervention was implemented to improve the language and problemsolving skills of four young mainstreamed children with developmental disabilities. To ensure that the children had a clear concept of Logo, a specially designed scope and sequence curriculum, with instructional aids, was developed. The children were tested in language and cognitive processing and gain scores were analysed after the intervention. While there were no statistically supportable conclusions attesting to the benefit of Logo in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Particular interest has been shown in the effects on development of mathematical thought, the transfer of acquisitions to other situations and effects in the shorter or longer term. Published results are contradictory and only a few examples will be given here, Some authors have found no effect on logical development expressed as Piagetian stages (Howell, Scott, & Diamond, 1987) nor on cognitive or language abilities (Bailey, 1992). In an extensively documented review of the question, Salomon and Perkins (1987) noted that the transfer of acquisitions to remote tasks was almost never seen.…”
Section: Methods and Their Objectivesmentioning
confidence: 99%
“…Particular interest has been shown in the effects on development of mathematical thought, the transfer of acquisitions to other situations and effects in the shorter or longer term. Published results are contradictory and only a few examples will be given here, Some authors have found no effect on logical development expressed as Piagetian stages (Howell, Scott, & Diamond, 1987) nor on cognitive or language abilities (Bailey, 1992). In an extensively documented review of the question, Salomon and Perkins (1987) noted that the transfer of acquisitions to remote tasks was almost never seen.…”
Section: Methods and Their Objectivesmentioning
confidence: 99%